2017
DOI: 10.3389/fmicb.2017.01400
|View full text |Cite
|
Sign up to set email alerts
|

Wood Ash Induced pH Changes Strongly Affect Soil Bacterial Numbers and Community Composition

Abstract: Recirculation of wood ash from energy production to forest soil improves the sustainability of this energy production form as recycled wood ash contains nutrients that otherwise would be lost at harvest. In addition, wood-ash is beneficial to many soils due to its inherent acid-neutralizing capabilities. However, wood ash has several ecosystem-perturbing effects like increased soil pH and pore water electrical conductivity both known to strongly impact soil bacterial numbers and community composition. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 87 publications
(127 reference statements)
7
49
1
Order By: Relevance
“…The increase in 16S rRNA gene copy numbers after ash amendment (up to 12 t ha −1 and 90 t ha −1 for the agricultural and forest soil, respectively) is consistent with other reports of increasing bacterial numbers after wood ash application (Bååth & Arnebrant, 1994; Fritze et al , 2000; Perkiömäki & Fritze, 2002; Bang-Andreasen et al , 2017; Vestergård et al , 2018). The large increase in the forest soil is further consistent with the increased pH as most bacteria thrive better at pH around 7 (Rousk et al , 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The increase in 16S rRNA gene copy numbers after ash amendment (up to 12 t ha −1 and 90 t ha −1 for the agricultural and forest soil, respectively) is consistent with other reports of increasing bacterial numbers after wood ash application (Bååth & Arnebrant, 1994; Fritze et al , 2000; Perkiömäki & Fritze, 2002; Bang-Andreasen et al , 2017; Vestergård et al , 2018). The large increase in the forest soil is further consistent with the increased pH as most bacteria thrive better at pH around 7 (Rousk et al , 2009).…”
Section: Discussionsupporting
confidence: 91%
“…We found that ash-amendment strongly increased soil pH, which is a strong driver of microbial community composition and functioning (Fierer & Jackson, 2006; Rousk et al , 2010) also after wood ash application (Frostegård et al , 1993; Zimmermann & Frey, 2002; Högberg et al , 2007; Peltoniemi et al , 2016; Bang-Andreasen et al , 2017). DOC and phosphate concomitantly increased.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The effects of wood ash on soil pH and nutrient status of the soil, however, are only shortlived due to the high solubility of K and Na oxides, hydroxides and carbonates which leach quickly (Ulery et al, 1993). Furthermore, the high K availability, general salinity (high electric conductivity (EC)) and high pH, change the soil chemistry rapidly which can result in toxicity in plants and soil organisms and shifts in soil microbial composition (Augusto et al, 2008;Bang-Andreasen et al, 2017;Demeyer et al, 2001;Etiegni et al, 1991b;Jagodzinski et al, 2018;Qin et al, 2017;Staples and Van Rees, 2001). Therefore, means to create an ash-M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 containing material which supplies nutrients in a more controlled way makes the use of ash in forestry and agriculture much more attractive and therefore, reduces the amount of ash being landfilled and closes the nutrient loops.…”
Section: Introductionmentioning
confidence: 99%
“…Contaminant-free PPFA has great significance as a soil liming agent and fertilizer in agriculture and forestry [6,11]; however, its direct application requires safety precautions due to its undesirable handling and spreading characteristics and associated health risks [12,13]. Further, high pH and electrical conductivity values of pore water in wood ash might have perturbing effects on the microbial community [14]. In order to withstand extreme conditions, the bacteria may enter a dormant stage, thereby decreasing the microbial population and diversity and ultimately disturbing the ecological balance.…”
mentioning
confidence: 99%